Caracterização faciológica, petrográfica e geoquímica de conduto vulcânico da Formação Serra Geral, na Barragem de Água Vermelha, divisa MG/SP - Fernando Estevao R Crincoli Pacheco (2017)
This work shows information about a basaltic ring structure (BRS) of Serra Geral Formation, localized on Rio Grande riverbed between the cities of Iturama (MG) and Ouroeste (SP) and is going to be presented in the form of two papers. The first one shows a detailed geological mapping at 1:1000 scale, stratigraphic, petrographic and gravimetric analysis of the most well preserved of the BRS. The central flow, interpreted as a preserved lava lake, comprises basalt rich in vesicles and amygdales, spatters, ropy and degassing structures. The basal flow has massive basalt containing geodes filled with quartz or basalt. Above, the lava flows show massive basalt with vertical columnar jointing where is possible to identify the top and bottom of each individual flow, with gentle dips towards the perimeter of the structure. A prominent ring dyke dipping towards the lava lake presents horizontal columnar jointing and cuts the basal and central flows. The gravimetric analysis shows a weak negative Bouguer anomaly on the center of the BRS. The proposed model describes the volcanism of the region in three main steps: (1) fissure flow occurs with lava input; (2) this lava cools and crystallises cementing most of the fissures, promoting the formation of localized central conduits; and (3) the presence of dissolved gas in lava produces ring and radial fractures around the solidified lava lake. The magma uses some of the ring fissures to ascend and the following lava flows assume the ring shape of the dyke vent. The second one shows detailed analyses of petrography, lithochemistry and mineral chemistry. The BRS rocks, based on textures and structures, were divided into four groups (central flow, basal flow, main ring dyke and lava flow) with a very similar petrography, composed of plagioclase (labradorite-bytownite), clinopyroxene (augite) and oxide (titanomagnetite) with intergranular texture. The whole-rock geochemical analyses of the basal and lava flows allow classifying them as tholeiitic basalts of the Paranapanema magma-type. Geochemical data interpretation suggests an enriched magma source, with low degree of partial melting and high depth of melt generation and without significant crustal contamination. The BRS experienced fractional crystallization on the shallow magma chamber, influenced by new magma injections responsible for the pulses of effusion and explosion. Thus, the singularities of the BRS of Água Vermelha are important to the comprehension of the evolution of the PEMP.